KEANEKARAGAMAN JENIS KELELAWAR (Chiroptera) DI KEBUN RAYA SAMBAS KABUPATEN SAMBAS KALIMANTAN BARAT - Sella, Seravina; Prayogo, Hari; Erianto, Erianto (JURNAL HUTAN LESTARI, 2019)
Bats (Chiroptera) are the only mammals that have wings and move or move by flying. Bats can be found in habitats supporting his whereabouts, among them the Sambas Botanical Gardens (KRS). This study aims to obtain data about the species of bats found in the Sambas Botanical Gardens. The method used in research is the of exploration, samples are taken using the method of trapping with a mist net placed purposive in 6 research stations that are near the building, around fruit trees, riparians, boundary of Sambas Botanical Garden with oil palm plantations, foothills and open areas. Studies show as many as 6 species of bats were found in the KRS. The Megachiroptera 4 species among them are Balionycteris maculata, Cynopterus brachyotis, Cynopterus horsfieldi and Cynopterus titthaecheilus, while the Microchiroptera group are 2 species of Saccolaimus saccolaimus and Tylonycteris pachypus.Â  Based on data analysis, the index value for species richness is (DMg = 1.6), diversity (H '= 1.41), evenness (E = 0.75) and dominance (C = 0.24).Keywords: Bats, Diversity, Sambas Botanical Gardens